Low-frequency noise investigation of n-channel 3D devices - De Andrade, Maria Glória Caño [UNESP]; Martino, João Antonio; Simoen, Eddy; Claeys, Cor (Elsevier, 2015)
In this paper, the low-frequency (LF) noise in standard n-channel triple-gate Bulk FinFETs has been experimentally investigated with variation in the fin widths (WFin), channel lengths (L) and gate dielectric. The origin of the noise will be analyzed in order to understand the physical mechanisms involved in 3D device architectures. Although the device scaling brings the idea of noise reduction, we show the opposite behavior because already single electron trapping has a marked impact on the device operation. Significant variation in the noise spectral density has been observed, which is related to the random occurrence of excess Lorentzian components (1/f2-like), associated with generation-recombination (GR) noise. In addition, the gate-voltage-dependent GR noise peaks have been studied, which are assigned to gate oxide traps.
Keywords: 3D devices; Bulk; FinFET; Flicker noise; Generation-recombination noise; Low-frequency noise